2022
DOI: 10.1590/1982-0275202239200136
|View full text |Cite
|
Sign up to set email alerts
|

Fear and anxiety in professionals about COVID-19: Brazilian versions of measures

Abstract: The objective of this study was to adapt and verify the psychometric properties of the Fear of COVID-19 Scale and Coronavirus Anxiety Scale, from the data collection conducted with professionals who work directly in the fight against COVID-19 in Brazil. A total of 232 professionals participated (Mage = 32.9; SD = 7.6), most of them female (68.1%), who answered the Fear of COVID-19 Scale, the Coronavirus Anxiety Scale, and the Depression, Anxiety, and Stress Scale instruments and a sociodemographic questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…These findings are aligned with previous network research on COVID-19 fear among the general population in Iran, Bangladesh, and Norway ( 46 ). The most common symptom of FCV-19S, palpitations, was observed in this study and also previous research among the general population ( 86 ) and HPs ( 87 ). Additionally, recent research showed that having palpitations was a significant predictor of anxiety, depression, and insomnia ( 88 ).…”
Section: Discussionsupporting
confidence: 89%
“…These findings are aligned with previous network research on COVID-19 fear among the general population in Iran, Bangladesh, and Norway ( 46 ). The most common symptom of FCV-19S, palpitations, was observed in this study and also previous research among the general population ( 86 ) and HPs ( 87 ). Additionally, recent research showed that having palpitations was a significant predictor of anxiety, depression, and insomnia ( 88 ).…”
Section: Discussionsupporting
confidence: 89%